Histopathology of Striped Catfish (Pangasianodon hypophthalmus) Fed with Moringa Leaf Addition and Maintained in Photoperiod Aquaponics - Zulmi Arnoli; Windarti Windarti; Morina Riauwaty (Faculty of Fisheries and Marine, Universitas Riau, 2024)
Moringa is one of the plants with high nutrients and antioxidants and can improve fish's immune system. This study aimed to look at the structure of the skin and kidney tissue of striped catfish fed with feed containing Moringa leaf flour after being tested for Aeromonas hydrophila bacteria. This research was conducted from January to May 2024 at the Biotechnology Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau, and fish histology observations were made at the Aquatic Biology Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Riau. The method used in this study is an experimental method by applying a one-factor Completely Randomized Design (CRD) with five levels of treatment and three replicates, namely KN (without moringa leaves and A. hydrophila challenge test), KP (without moringa leaves and challenged with A. hydrophila), P1 (dose of 10 g/kg feed), P2 (dose of 15 g/kg feed), P3 (dose of 20 g/kg feed). The results showed that most organ tissues were still in a normal state. The best dose of moringa flour addition to feed is 10 g/kg feed (P1). Fish tissue structure in P1 has damage such as hypertrophy, hemorrhage, and lipofuscin pigment on fish skin. Fish survival during the study was 97.67%.